Swelling resistance and tensile strength of natural rubber (NR) and carboxylated nitrile-butadiene rubber (XNBR) latex blends: article / Azemi Samsuri, Amir Hashim Md Yatim and Ruhida Ab. Rahim - Samsuri, Azemi; Md Yatim, Amir; Ab. Rahim, Ruhida (2008)
Natural rubber (NR) latex glove possesses superior mechanical properties compared to many synthetic glove, but it has a relatively poor oil swelling resistance and this limit the application in food handling industry, especially for food containing oils and fats. In this study, differently sulphur content crosslinked NR latex and NR blended with compounded carboxylated nitrile (XNBR) latex to improve the films’ oil swelling resistance. The tensile properties of NR latex film and NR:XNBR latex film was evaluated before and after exposure to cooking oil. As expected, the increasing the XNBR content improved swelling resistance due to increase in the polarity, which reduced the oil mass uptake and decreased the diffusion coefficient. The results indicated that the optimum blend at a ratio 80 part NR to 20 part XNBR with 1.5 pphr sulphur content gave the optimum acceptable swelling resistance and tensile properties.